Analisis Kritis Sanad dan Matan Hadis tentang "Juhainah" sebagai Figur Terakhir Penghuni Neraka - Diah Pratiwi, Ayu; Syahminan, Mhd. (Kartika: Jurnal Studi Keislaman, 2026)
Hell and Paradise are realms whose existence and conditions are firmly believed by Muslims. Hell is understood to be inhabited by those who disbelieve and commit many sins, while Paradise is for those who have faith and perform righteous deeds. It is also part of Islamic belief that some people will remain eternally in Hell, whereas others will be taken out after a certain period of time. In the hadith literature, there are narrations describing an individual who will be the last to emerge from Hell. There is also a popular report identifying this individual by the name Juhainah. However, this name remains controversial in terms of its authenticity and the reliability of the narrations that mention it. Using a qualitative research approach based on library study, this research aims to clearly examine the figure of Juhainah. The hadith analysis employs the method of takhrij al-hadith, which includes sanad (chain of transmission) and matn (textual) criticism within the major hadith collections, referring to works of takhrij, sharh, and tarajum wa al-tabaqat to determine the validity of the reports. The findings of this study indicate that the exact number of those who will emerge from Hell whether a single individual or a group cannot be definitively established, and that the narrations mentioning the name Juhainah are deemed batil and therefore cannot be used as authoritative hujjah. Accordingly, this study is expected to serve as a reference that provides a comprehensive clarification regarding the figure of Juhainah